Thermal Performance of Reverse‐Layered Air‐Cooled Cylindrical Lithium Battery Pack Integrated with Staggered Battery Arrangement and Spoiler. Issue 5 (6th March 2022) - Zhang, Furen; Zhu, Yilin; Ge, Zhe
Abstract : In order to improve the cooling performance of the reverse layered air‐cooled cylindrical lithium‐ion battery pack, a structure optimization design scheme integrated with a staggered battery arrangement and longitudinal spoiler was proposed. Based on the computational fluid dynamics (CFD) method, the cooling performance of an air‐cooled battery thermal management system (BTMS) was studied, and the reliability of CFD calculation results was verified by the forced air cooling experiment of the battery pack. Firstly, the effect of a staggered arrangement of batteries on the cooling performance of the battery pack was explored. The results revealed that the hybrid staggered arrangement of the batteries greatly improved the heat dissipation performance of the cooling system. Compared with the initial condition, the maximum temperature ( T max ) and maximum temperature difference (Δ T max ) were reduced by 12.73 °C (24.96%) and 7.7 °C (87.8%), respectively. However, the problems of high temperature of batteries and poor temperature uniformity of the battery pack still existed. Secondly, the cooling performance of BTMS was further improved by constructing the structure integrated with hybrid staggered arrangement and longitudinal spoilers. The results respectively revealed that T max and Δ T max were decreased by 13.06 °C (25.6%) and 8.45 °C (96.35%). Finally, the influences of the length, thickness, and number of spoilers were discussed. Abstract : In this study, a structure optimization design scheme integrated with staggered battery arrangement and longitudinal spoiler is proposed. The effects of the staggered distance of batteries and the structural parameters of spoilers are investigated. The results illustrate that the method adopted in this work can effectively improve the heat dissipation of an air‐cooled battery thermal management system.